(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective : There is growing concern that exposure to arsenic during pregnancy can have adverse effects on the developing fetus. To investigate the effect of arsenic exposure on reproductive health outcomes this study was carried out. Materials and methods : This prospective birth cohort study was carried out by Harvard School of Public Health and Dhaka Community Medical College & Hospital in 2004 through the Sirajdikhan and Birahimpur community clinics as a pilot project. The study included 421 pregnancies at the time of enrollment. Water samples were collected at the time of enrollment and within one month of delivery from the tubewell of each participant identified as their primary source of drinking water. These samples were analyzed by inductively coupled plasma mass spectrometry. Results: Of 421 pregnancies, 38 women withdrew from the study or were lost to follow up (9.0%), 30 resulted in spontaneous abortion or miscarriage (7.1%), 32 were stillbirths (7.6%) and 321 were live births (76.2%). At the time of enrollment, the average drinking water arsenic exposure level was 31.6 ?g/L (standard deviation, 83.7 ?g/L; range, <1 880 ?g/L). The average drinking water level at one month post delivery was 26.1 ?g/L (standard deviation, 68.2 ?g/L, range: <1 to 460 ?g/L) which indicated that exposure to arsenic contaminated drinking water decreased during pregnancy. However, 31.9% of all participants exceeded the World Health Organizations recommended drinking water arsenic level of 10 ?g/L and 16.9% exceeded the Bangladesh drinking water arsenic regulation of 50 ?g/L. Sixty-three (40.9%) of all women reported an illness during this pregnancy. The odds of reporting any illness during the current pregnancy was 51% higher for those women who used a tubewell that contained more than the Bangladesh drinking water standard during their pregnancy compared to pregnant women who used a tubewell that contained less than 50 ?g As/L adjusting for maternal age, maternal education, and pregnancy history (odds ratio, 1.51; 95% confidence interval, 0.28, 8.16). Of the 321 live births, 64 (15.2%) had a birthweight less than 2500 grams and were classified as low birthweight. The odds of a low birthweight infant was 32.3% greater for those women who used a tubewell that contained more than the Bangladesh drinking water standard during their pregnancy compared to pregnant women who used a tubewell that contained less than 50 ?g As/L adjusting for maternal age, maternal education, gestational age, infant sex, spouses education, mothers weight gain during the first 28 weeks, chewing betel nuts, reporting any illness during pregnancy, environmental tobacco smoke, and pregnancy history (odds ratio, 1.32; 95% confidence interval, 0.19, 9.17). In this sample, 35 infants were born at less than 37 weeks gestational age (8.3%) and were classified as preterm infants. The odds of a preterm infant was 84% greater for those women who used a tubewell that contained more than the Bangladesh drinking water standard during their pregnancy compared to pregnant women who used a tubewell that contained less than 50 ?g As/L adjusting for maternal age, maternal education, spouses education, mothers weight gain during the first 28 weeks, environmental tobacco smoke, and pregnancy history (odds ratio, 1.84; 95% confidence interval, 0.81, 4.17). Conclusion: Arsenic exposure during pregnancy contributed to adverse maternal child health outcomes. It is important to note that none of these associations reached statistical significant and it will be important to confirm these associations in the complete dataset. Bangladesh J Obstet Gynaecol, 2013; Vol. 28(2) : 76-81